Palladium-Nanoparticle-Catalyzed Matsuda–Heck Reaction in Water - Gaikwad, Dipak S.; Pore, Dattaprasad M. (Synlett, 2012)
An eco-friendly, simple method for Matsuda–Heck arylation of olefins catalyzed by in situ formed Pd nanoparticles is described in water operable at ambient temperature. A variety of arenediazonium salts were coupled with olefins under ligand-free and aerobic conditions in high yields and stereoselectivity.
Keywords: Matsuda–Heck; Pd nanoparticles; triton X 100; diazonium salts; eco-friendly